Higher dose dobutamine stress MR imaging in repaired tetralogy of fallot: Observer variance of volumetric assessment compared with normal volunteers. Issue 6 (23rd May 2013) - Parish, Victoria; Valverde, Israel; Kutty, Shelby; Head, Catherine; Greil, Gerald F.; Schaeffter, Tobias; Razavi, Reza; Beerbaum, Philipp
<x xml:space="preserve">Abstract</x> Purpose To investigate changes in image quality and observer variance between rest and higher‐dose dobutamine stress MR imaging (DS‐MR) in tetralogy of Fallot (TOF) patients and in a group of normal healthy volunteers using both axial and short axis orientation for cardiac volumetric assessment. Materials and Methods Eighteen adult patients (age 34 ± 13) with TOF and severe pulmonary regurgitation and 10 healthy volunteers underwent ventricular MR volumetry at baseline and during dobutamine infusion of 10 μg/kg/min and 20 μg/kg/min. Inter‐observer and intra‐observer agreement was calculated by coefficient of variance (COV). Results Inter‐observer comparison showed good agreement for left ventricle (LV) and right ventricle (RV) end‐diastolic volumes at rest and both stress levels in TOF patients (axial geometry) and in normal volunteers (short axis). During dobutamine stress, the COV in TOF patients increased for LV end‐systolic volume (LV‐ESV) with each level, suggesting less agreement between observers. In contrast, RV‐ESV was much more comparable with a COV < 10 at each condition. All volumetric measurements in normal volunteers showed good inter‐observer agreement. Excellent intra‐observer agreement could be seen for all volumetric parameters with COV levels below 7. Conclusion Volumetric assessment during DS‐MR shows excellent inter‐observer agreement, except for LV‐ESV in the TOF patients at higher doses of dobutamine. The axial geometry appears to be reproducible for assessment of RV parameters, and could be considered superior to short axis imaging in patients with repaired TOF. J. Magn. Reson. Imaging 2013;38:1356–1361. © 2013 Wiley Periodicals, Inc.